Experimental Study on Utilization of Exhaust Gas of an I.C Engine - Ramana, P.V.; premKumar, B. Sudheer (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
With the increasing cost of energy of and the need to conserve the same, it has become absolute essential to save energy irrespective of its quantum in every field. In particular refrigeration and air conditioning systems consume a substantial amount of energy. In transportation of frozen foods the energy required by the refrigeration system can be supplied by the vehicle engine exhaust heat otherwise it goes as a waste heat to atmosphere. A refrigeration system which makes use engine exhaust heat without affecting the performance of the engine will be more useful in saving the energy.Our country is gaining foreign currency by exporting especially sea foods to countries like Japan etc,. These products are to be preserved at low temperatures. The transportation up to the cold storage in ships is to be done by refrigerated trucks. So the saving of energy in these refrigeration systems will be very much justified. In this present study an attempt is made to run a refrigerator which works on domestic Electrolux refrigeration system with the engine exhaust. An engine of 10.5 H.P is selected and the fridge available in the laboratory i.e Himalux 100 liters capacity is made use for this purpose. The electrical heating unit in the generating portion is removed and heat is supplied through the engine exhaust gases. The test results are very much satisfactory .we could run the refrigerator effectively without much fall in the engine efficiency. These test results give a hope that similar systems can be adopted on a refrigerated truck, which will be very much justified.